Optimal design of a solar-driven Kalina system for combined power and desalination purposes - Khanmohammadi, Shoaib; Genceli, Hadi; Pakseresht, Amirhossein; Bellotti, Daria (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
This research study presents a thermodynamic simulation and exergy analysis of a solar-powered Kalina cycle that is integrated with a reverse osmosis desalination (RO) module and a thermoelectric generator (TEG) system. A parabolic through solar collector (PTSC) provides the required heat to drive designed plant. The thermodynamic simulation and exergy examination of the proposed system are carried out using the Engineering Equation Solver (EES). A parametric study of the presented plant to show the primary parameters impacts on the system operation is conducted. The system in this study generates 212.7 kW of electrical power and 44.46 m3/h. The total energy efficiency of the plant is 24.3 %. The inlet thermal energy from PTSC is 876.5 kW. In addition, the thermoelectric module generates 7.26 kW electrical power. Carried out analyses show that the recuperator has the most significant exergy destruction rate among all system components, with 303.2 kW. The unit responsible for the second major exergy destruction value associated with the RO unit, which accounts for 74.22 kW. To examine the influence of influences of parameters like direct normal irradiance (DNI), turbine inlet pressure, and mass flow rate of the Kalina cycle the system case study is presented. It can be observed that increasing DNI parameter from 750 W/m2 to 1000 W/m2 leads in a net output power increment from 279.1 kW to 372.1 kW and increasing fresh-water production from 41.64 m3/h to 48.09 m3/h. Moreover, the calculation shows that increasing DNI has a positive impact on the TEG unit output power too. Enhancing the inlet turbine pressure increases both net output power and fresh-water production by reverse osmosis unit while this increment diminishes the thermoelectric unit electrical output. It can be observed that increasing turbine inlet pressure from 110 kPa to 200 kPa, increases net output power and fresh-water production by about 6.08 % and 3.5 %, respectively.
Keywords: PTSC; Reverse osmosis; Kalina cycle; Exergy analysis; Direct normal irradiance; ORGANIC RANKINE-CYCLE; ENERGY; OPTIMIZATION; EXERGY; CONVERSION; Energy & Fuels